Suicide Notes: Exaggerations by Males and Females - Kusumastuti, Purbo; Apriana, Aulia; Basthomi, Yazid (Journal of Language and Health, 2020)
Touching into the gender differences between males and females in expressing the use of exaggeration expressions, this study analyzes the relevant data using the LIWC tool, the HIP method, and the deficit and difference theories. This study found that in relation to the gender stereotypes, both males and females speak differently, yet also demonstrate similarities. Both the male and female subjects express emotions equally in the language production; yet, the negative emotions are dominated by the males, and the positive emotions are dominated by the females. The difference of emotion productions influences the differences in the males’ production of exaggeration expressions, such as empty adjectives, italic expressions, and hyperbole by the female subjects.